A mixed method feasibility and acceptability study of a flexible intervention based on acceptance and commitment therapy for patients with cancer - Bourgognon, François; Bechet, Denise; Huin-Schohn, Cécile; Strelow, Aurélia; Demarche, Laëtitia; Guillou, Mireille; Adam, Virginie; Fall, Estelle; Omorou, Abdou Yacoubou (Frontiers in Psychology, 2024)
Propose: This study aimed to propose an innovative, open and circular program that combines acceptance and commitment therapy (ACT) and mindfulness practices. We assessed its feasibility, acceptability and first signs of its effect on psychological well-being in cancer support treatment.Methods: A single-centre, single-arm, uncontrolled study was performed. Forty adult patients with non-metastatic prostate or breast cancer, newly diagnosed or undergoing treatment (chemotherapy, radiotherapy, hormone therapy), were recruited. Three cycles of three MAEva program sessions (MAEva: Mindfulness meditation, Acceptance and Commitment to values program) over nine consecutive weeks were proposed. During the total of twelve weeks followup, after attending the first session, patients were free to attend subsequent sessions.Results: Adherence to the study was high, with participation in an average of 6.8 out of nine sessions. Eight patients attended all sessions over the three cycles, and 90 percent participated in at least one cycle. Furthermore, attendance was associated with a statistically significant improvement in Quality of Life (QoL). Each additional session was associated with a mean increase in overall QoL score of more than one point (β=1.09 [0.13; 2.04], p=0.02). The fatigue dimensions decreased with session attendance: physical (β=-2.24 [-3.63; -0.85]), emotional (β=-2.60 [-4.11; -1.09]) and interference with daily life (β=-2.33 [-3.95; -0.72]). The qualitative section demonstrated that patients learned skills and shared their ability to "let go". Patients rated the degree of importance of the program at 8.36/10 (SD ±1.64).This study highlights the feasibility and acceptability of an original program that combines ACT and mindfulness practices in cancer patients. Future studies are required to demonstrate the efficacy of the MAEVA program.The MAEva pilot study is registered with ClinicalTrials.gov under the identifier NCT04751201.